PENGARUH DISKON HARGA, KUALITAS PRODUK DAN BELANJA HEDONIS TERHADAP PEMBELIAN IMPULSIF - Achmad Nurfauzi; Edy Purwanto (Ekomania, 2024)
Advances in information technology have encouraged an increase in the number of internet users in Indonesia. This research was conducted on Generation Z in Sumenep Regency. The purpose of this research is to find out and analyze the effect of price discounts on impulse buying, to find out and analyze the effect of product quality on impulsive buying, to find out and analyze the effect of Hedonic Shopping on impulsive buying. This research uses a quantitative approach. The number of respondents used was 114 respondents taken using purposive sampling technique. The respondent criteria used in this research are consumers who use and have made impulse purchases, consumers who have Classic - Gold member accounts and Generation Z consumers. Data collection was carried out by distributing questionnaires to respondents directly. Based on the research results, it shows that the price discount variable has a positive and significant influence on impulsive purchases in the Shopee marketplace, the product quality variable has a positive and significant influence on impulsive purchases in the Shopee marketplace, and the hedonic shopping variable has a positive and significant influence on impulse purchases in the Shopee marketplace.